A Novel Regulatory Mechanism of Smooth Muscle α-Actin Expression by NRG-1/circACTA2/miR-548f-5p Axis. Issue 6 (1st September 2017) - Sun, Yan; Yang, Zhan; Zheng, Bin; Zhang, Xin-hua; Zhang, Man-li; Zhao, Xue-shan; Zhao, Hong-ye; Suzuki, Toru; Wen, Jin-kun
Abstract : Rationale: : Neuregulin-1 (NRG-1) includes an extracellular epidermal growth factor–like domain and an intracellular domain (NRG-1-ICD). In response to transforming growth factor-β1, its cleavage by proteolytic enzymes releases a bioactive fragment, which suppresses the vascular smooth muscle cell (VSMC) proliferation by activating ErbB (erythroblastic leukemia viral oncogene homolog) receptor. However, NRG-1-ICD function in VSMCs remains unknown. Objective: : Here, we characterize the function of NRG-1-ICD and underlying mechanisms in VSMCs. Methods and Results: : Immunofluorescence staining, Western blotting, and quantitative real-time polymerase chain reaction showed that NRG-1 was expressed in rat, mouse, and human VSMCs and was upregulated and cleaved in response to transforming growth factor-β1. In the cytoplasm of HASMCs (human aortic smooth muscle cells), the NRG-1-ICD participated in filamentous actin formation by interacting with α-SMA (smooth muscle α-actin). In the nucleus, the Nrg-1-ICD induced circular ACTA2 (alpha-actin-2; circACTA2) formation by recruitment of the zinc-finger transcription factor IKZF1 (IKAROS family zinc finger 1) to the first intron of α-SMA gene. We further confirmed that circACTA2, acting as a sponge binding microRNA (miR)-548f-5p, interacted with miR-548f-5p targeting 3′ untranslated region of α-SMA mRNA, which in turn relieves miR-548f-5p repression of the α-SMA expression and thus upregulates α-SMA expression, thereby facilitating stress fiber formation and cell contraction in HASMCs. Accordingly, in vivo studies demonstrated that the localization of the interaction of circACTA2 with miR-548f-5p is significantly decreased in human intimal hyperplastic arteries compared with normal arteries, implicating that dysregulation of circACTA2 and miR-548f-5p expression is involved in intimal hyperplasia. Conclusions: : These results suggest that circACTA2 mediates NRG-1-ICD regulation of α-SMA expression in HASMCs via the NRG-1-ICD/circACTA2/miR-548f-5p axis. Our data provide a molecular basis for fine-tuning α-SMA expression and VSMC contraction by transcription factor, circular RNA, and microRNA. Abstract : Supplemental Digital Content is available in the text.